Integrative redescription of Glomeris cingulata C. L. Koch, 1847, an almost forgotten microendemic pill millipede (Diplopoda, Glomerida, Glomeridae) - Wesener, Thomas (Zootaxa, 2024)
Among the more than 80 species of the common pill millipede genus Glomeris Latreille, 1803, there are several microendemic species that have not been recorded for the last 80–120 years. To discover whether these species are colour morphs of widespread species or true local endemics is important from a conservation point of view as well as for understanding the biogeography and evolution of the group. The author received three specimens that were morphologically identical to C. L. Koch's 175-year-old first description of Glomeris cingulata Koch, 1847 from the Triglav Mountain in Slovenia, close to the border with Italy. No clear specimen-based records are available for G. cingulata and the type specimen is apparently lost. In order to clarify the taxonomy of this microendemic species, an integrative redescription was conducted, including scanning electron microscopy and DNA barcoding. Glomeris cingulata is a distinct species, with genetic distances of 12.6–15.5% compared to the seven syntopic and numerous other widespread Glomeris species. Based on characters of the first description and following other authors, the synonymy of Glomeris cingulata intercedens Latzel, 1884 under Glomeris transalpina Koch, 1836 is confirmed. The dark colour with posterior red bands closely resembles that of some other high-altitude Glomeris species like G. transalpina Koch, 1836, Glomeris aurita Koch, 1847 and Glomeris oropensis Verhoeff, 1936. Glomeris cingulata is genetically close to, but distant enough from the small-bodied and widespread taxa like Glomeris pustulata Latreille, 1804 and Glomeris tetrasticha Brandt, 1833.